MEDIATING ROLE OF WORK ENGAGEMENT IN THE RELATIONSHIP BETWEEN SAFETY CLIMATE AND SAFETY PERFORMANCE AMONG ELECTRIC AND ELECTRONICS COMPANIES IN MALAYSIA - Noor Azlan, Shakirah; Abdul Wahab, Shah Rollah; Nho, Yong Jin; Mohd Mustafa, Mohd Alwi; Abu Bakar, Khaironisa (Journal of Human Capital Development (JHCD), 2022)
ABSTRACT Accidents occurring at the workplace affect an organization’s financial, productivity, and employees’ commitment to continue working with the organization. Previous studies have shown that organizational environment and effective motivation of employees affect to safety performance in the organization. Therefore, this paper aims to investigate the mediating role of work engagement in the relationship between safety climate and safety performance in seven (7) selected electric and electronic manufacturing companies at Perak, Malaysia. The data were obtained from 400 workers operators’ workers through questionnaire distributed were then analysed by using the Smart PLS. Findings revealed that work engagement plays a significant role as a mediator in the relationship between safety climate and safety performance based on the findings from indirect effect. Keywords: Work Engagement; Safety Climate; Safety Performance; Smart PLS